IMPLEMENTASI BIM (BUILDING INFORMATION MODELING) TERHADAP PENINGKATAN EFISIENSI DAN AKURASI PADA PERHITUNGAN ESTIMASI BIAYA PROYEK PEMBANGUNAN JALAN JALUR LINTAS SELATAN (JLS) LOT 3 PANTAI SERANG – SUMBERSIH - Maura Muzdhalifa, Rencany; Pahang Putra, I Nyoman Dita; Widowati, Elok Dewi (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
The development of technology has significantly influenced the construction industry, introducing innovations that enhance project execution efficiency and accuracy. One of the notable advancements is Building Information Modeling (BIM) is a digital representation of a building that fully illustrates its form, size, and functional aspectsThis study aims to implement Building Information Modeling (BIM) for Quantity Take Off (QTO) using Autodesk Revit 2025 and compare its results with conventional methods in terms of volume and cost estimation accuracy. The research object is the South Cross Road Construction Project (JLS) Lot 3 from Pantai Serang to Sumbersih. This comparative quantitative study utilizes Detail Engineering Design (DED) documents and 3D modeling with Autodesk Revit 2025. The findings show that BIM-based QTO produces more accurate and efficient cost estimations, especially in complex calculations such as cut and fill operations. The BIM method resulted in a total project cost that was 13.73% higher than the conventional method, primarily due to more precise terrain modeling. This research is expected to be a reference for improving the accuracy of infrastructure project cost estimation.